PREVENTION AND CONTROL OF CHRONIC DISEASES IN VULNERABLE POPULATIONS: APPROACHES IN FAMILY MEDICINE - Antônia Rocha Fiorott, Maria; Brandão Coelho, Ingrid; Dadalto Scarpati, Elza; Martins Eller, Lara; Sarlo Pinheiro, Alice; Siqueira Neto, José; Altoé Pipa Silva, Ivelize; Maia Cruz Brazuna, Ricardo; Cesar Ferreira, Alex; Lofêgo Olmo, Nicolle; Maria Moreno Lobo, Marcelle; Castro Narduci, Jessica; et al. (Health and Society, 2024)
Chronic diseases such as diabetes, hypertension and cardiovascular diseases are prevalent in vulnerable populations, who often face difficulties in accessing adequate medical care. Primary care, especially family medicine, plays a central role in the prevention and control of these diseases, as it offers continuous, comprehensive and personalized care, focused on health promotion and the prevention of complications. This model of care is especially effective in communities that face economic, social and cultural barriers, allowing for early intervention and appropriate management of chronic conditions. The aim of this study is to analyze strategies for the prevention and control of chronic diseases in vulnerable populations, with a focus on family medicine. The aim is to identify effective approaches that can be used to improve the quality of life of these populations and reduce the incidence and progression of chronic diseases. The research was carried out through a qualitative literature review, focusing on articles published between 2017 and 2022. The aim was to explore the advances and challenges in the management of chronic diseases, with an emphasis on primary health practices, the impact of social determinants of health, and the role of technologies such as telemedicine in the management of these conditions. By providing continuous and comprehensive care, family medicine uses various strategies to prevent and control chronic diseases. These include regular patient follow-up, early screening for conditions such as hypertension and diabetes, and health education, which guides individuals on healthy behaviors and self-care. In addition, disease monitoring programs and interventions such as modifying eating habits and promoting physical activity have shown positive results in the management of chronic diseases. However, there are still significant challenges, such as the scarcity of resources and the lack of qualified professionals, which limit the effectiveness of these approaches in certain regions and social groups. Overcoming these barriers requires a joint effort between health professionals, managers and public policies. It is concluded that family medicine is a fundamental approach to the control and prevention of chronic diseases, especially in vulnerable populations. The strategies adopted in this model of care, such as continuous monitoring, health education and early intervention, have shown significant results in improving quality of life and reducing complications associated with chronic diseases. However, in order to optimize the results, it is necessary to overcome challenges related to access and the training of professionals, as well as ensuring adequate support for the implementation of public health programs that favour the population in situations of vulnerability. Implementing efficient public policies and expanding access to primary health care are essential to achieving effective control of chronic diseases.